A Concise Organocatalytic Route to Protected (2S,4R)-4-Hydroxyornithine and (+)-Pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential α-aminoxylation/α-amination reaction and Horner–Wadsworth–Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; amination; amino alcohols; Wittig reaction; cyclization; enantioselectivity